Which NICS method is most consistent with ring current analysis? Assessment in simple monocycles. Issue 24 (10th April 2018) - Báez-Grez, R.; Ruiz, Lina; Pino-Rios, R.; Tiznado, W.
Abstract : A linear relationship between NICS zz, π and NICSπ, σ with their current strength counterparts is shown. The comparative analysis was performed in simple and representative monocycles. Abstract : The aromaticity of benzene, Al4 2− cluster, cyclopropane, borazine and planar cyclooctatetraene (COT) was analyzed according to different strategies based on nucleus-independent chemical shift (NICS) computations. The analysis of NICS-components evolution along the main molecular axis seems to be the most adequate and simplest strategy to predict the aromatic or antiaromatic character of the studied systems. Moreover, the analysis of the σ- and π-electron contributions to the out-of-plane component of NICS (NICS zz ) leads to the same qualitative and quantitative conclusions previously obtained by the analysis of the magnetically induced ring current densities.